2008
DOI: 10.1007/s11249-007-9291-0
|View full text |Cite
|
Sign up to set email alerts
|

Contact Fatigue Analysis of a Dented Surface in a Dry Elastic–Plastic Circular Point Contact

Abstract: The present article proposes a methodology for the computational analysis of damage induced in the vicinity of dents in a dry circular point contact under repeated rolling. The failure risk is evaluated through the use of the Dang Van multiaxial fatigue criterion. The dent is a typical surface defect encountered in rolling element bearings when operating in contaminated environments. It is usually created by a solid particle not removed by seals or filters when passing through an EHL conjunction. Since local p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…This has been shown in several experimental studies 23,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]51 and theoretical studies. 86,89,91,96,[105][106][107][108][109][110][111] For example, Ai and Nixon 110 found that the fatigue life is strongly influenced by the indentation area density and dent slope, particularly for slopes over 5 . The effect of a dent's slope on fatigue life of the dented surface has also been shown by Lubrecht et al, 111 who found that the reduction of life is proportional to the depth of the dent and inversely proportional to its wavelength in line contacts.…”
Section: Needelman and Zaretskymentioning
confidence: 99%
“…This has been shown in several experimental studies 23,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]51 and theoretical studies. 86,89,91,96,[105][106][107][108][109][110][111] For example, Ai and Nixon 110 found that the fatigue life is strongly influenced by the indentation area density and dent slope, particularly for slopes over 5 . The effect of a dent's slope on fatigue life of the dented surface has also been shown by Lubrecht et al, 111 who found that the reduction of life is proportional to the depth of the dent and inversely proportional to its wavelength in line contacts.…”
Section: Needelman and Zaretskymentioning
confidence: 99%
“…The contact solver may be also coupled with FEM to account for the flexibility of the structure and used as a structural zoom when a finer mesh is needed for the contact . The method has since been developed and improved in several ways by the group of Nélias at INSA-Lyon Gallego et al, 2006Gallego and Nélias, 2007;Antaluca and Nélias, 2008) and the group of Wang and Keer at Northwestern University Liu et al, 2007;Chen et al, 2008aChen et al, ,b, 2007Wang, 2008, 2009;Wang et al, 2009) to account for various plasticity models and tangential effects including running-in and fretting wear. One interesting improvement is due to Zhou et al (2009) who utilized a combination of three-dimensional and two-dimensional fast Fourier transform algorithms to decrease both the memory space allocated and the computing time.…”
Section: Contact Solvermentioning
confidence: 99%
“…In this investigation, a criterion was presented in order to evaluate the possibility of particles entrapment. ANTALUCA and NELIAS [22] studied the contact fatigue around dents in a dry circular point contact under repeated rolling. They proposed a new methodology of analysis using the Dang Van multi-axial fatigue criterion to evaluate the damage risk.…”
Section: Introductionmentioning
confidence: 99%